Antiproliferative Efficacy of N-(3-chloro-4-fluorophenyl)-6,7-dimethoxyquinazolin-4-amine, DW-8, in Colon Cancer Cells Is Mediated by Intrinsic Apoptosis - Rabin Neupane; Saloni Malla; Mariam Sami Abou-Dahech; Swapnaa Balaji; Shikha Kumari; Digambar Kumar Waiker; N. S. Hari Narayana Moorthy; Piyush Trivedi; Charles R. Ashby; Chandrabose Karthikeyan; Amit K. Tiwari (Molecules, 2021)
A novel series of 4-anilinoquinazoline analogues, DW (1–10), were evaluated for anticancer efficacy in human breast cancer (BT-20) and human colorectal cancer (CRC) cell lines (HCT116, HT29, and SW620). The compound, DW-8, had the highest anticancer efficacy and selectivity in the colorectal cancer cell lines, HCT116, HT29, and SW620, with IC50 values of 8.50 ± 2.53 µM, 5.80 ± 0.92 µM, and 6.15 ± 0.37 µM, respectively, compared to the non-cancerous colon cell line, CRL1459, with an IC50 of 14.05 ± 0.37 µM. The selectivity index of DW-8 was >2-fold in colon cancer cells incubated with vehicle. We further determined the mechanisms of cell death induced by DW-8 in SW620 CRC cancer cells. DW-8 (10 and 30 µM) induced apoptosis by (1) producing cell cycle arrest at the G2 phase; (2) activating the intrinsic apoptotic pathway, as indicated by the activation of caspase-9 and the executioner caspases-3 and 7; (3) nuclear fragmentation and (4) increasing the levels of reactive oxygen species (ROS). Overall, our results suggest that DW-8 may represent a suitable lead for developing novel compounds to treat CRC.